Converting a social network into a brand network: how brand profile on Facebook is used as an online marketing communication tool - Saransomrurtai, Chayanin (Auckland University of Technology, 2011)
The rapid growth of social network sites, such as Facebook and MySpace, has recently received a great deal of attention from both academics and practitioners. Millions of users actively participate on social network sites. Facebook alone has more than 500 million registered users. Marketers have begun to recognise these social network sites as a new avenue to promote their brands online. Top businesses around the world create their brand profiles on popular social network sites. At the same time, research on social network sites is relatively scarce. Particularly, research investigating businesses’ practices of using the new media of virtual social network for their brands is very limited. The present study employs content analysis to investigate how top Global, Australian, Japanese, Swiss, and Taiwanese businesses use brand profile pages on Facebook as their online marketing communication tool. Differences in the use of brand profile pages as an online marketing communication tool across the above mentioned four countries and across industries are also examined. Overall, the results of the present research indicated that businesses with product brands were more likely to have brand profile pages on Facebook than their service counterparts. However, the practices of businesses with product brands and service brands on Facebook were not found to be much different. Similarly, it was found that there is not much difference in the use of brand profiles among brands from different countries and industries. The lack of differences might imply that businesses tend to use only basic features of their brand profile pages and are not likely to develop distinctive content. Moreover, several tools which have the potential to be valuable resources to obtain feedback from consumers, such as polls and discussions, were found to be underutilised. The interesting finding is that there is an association between businesses’ use of brand profile pages and brand value. However, the direction of the relationship could not be established. Several implications and future research opportunities are provided in the dissertation.
Keywords: Facebook; Content analysis; Social network; Online marketing communication; SNS; Online branding